Estudo das propriedades ópticas e elétricas dos sistemas laponita e nanocompósitos de laponita/pontos quânticos - Braga, Amanda da Silva (2019)
Laponite is widely studied lamellar synthetic nanoclay that when added to a polar solvent occurs colloidal dispersions of its nanodisks that lead the system through a liquid-solid transition over time. Due to this behavior nanoclay is used in various industrial applications as rheological modifier of materials, such as paints, cleaning and personal hygiene products, among others. In addition, due to its lamellar structure, Laponite has been widely used in the preparation of nanocomposites. The addition of other material to the Laponite system can affect the liquidsolid transition, as well as the system can alter the properties of this material. In this work, we investigate the behavior of the liquid-solid transition of the Laponite system and the nanocomposites formed by Laponite and colloidal quantum dots of cadmium selenide (CdSe) and cadmium telluride (CdTe). The behavior was investigated by means of the study of the optical and electrical properties of the Laponite systems and Laponite/quantum dots nanocomposites formed by the techniques of optical and electrical characterization. By means of the Dynamic Light Scattering technique, the liquid-solid transition of samples with a clay concentration of 4,0% by weight in water was observed. This transition was not evidenced by the IxV and Ixt electrical measurements. The electrical measurements and some of the scattering were carried out by means of experimental apparatus developed by our group during the accomplishment of this work. The liquid-solid transition of the Laponite/CdTe quantum dots nanocomposites was investigated by light scattering technique. It was observed macroscopically that the CdTe quantum dots accelerated the transition and that the emission intensity was decreased. It was not possible to perform scattering measurements on Laponite/CdSe quantum dots nanocomposites because the sample became opaque during the functionalization process of the quantum dots. The CdSe quantum dots produced by the hot-injection syntesis, presented different sizes and light emission of different colors. These were characterized by UV-Vis Absorption Spectroscopy and Photoluminescence techniques.